Measurement of frequency deviation by using Arduino Uno - al-Rawi, Widad Jasim Hammudi; al-Dabbagh, Nadhirah Hasib Tawfiq (Engineering and Technology Journal, 2015)
هدفت هذه الدراسة إلى بناء و تطبيق تقنية جديدة في حساب و تصحيح انحراف التردد في منظومة توليد القدرة. تقنيات عديدة استخدمت لقياس هذا الانحراف. واحدة منها لوح الآردوينو – الذي يستخدم المتحكم الدقيق. Atmega 328 هذا اللوح ذو المتحكم الدقيق سهل الاستخدام، دقيق، مع جدوى اقتصادية و ذو حلول مرنة لمشاكل الهدف الرئيسي لهذه الدراسة هو قياس انحراف التردد بواسطة المسيطر الدقيق و عرضه على شاشة حاسوب أو شاشة (LCD) أو كلاهما. كذلك، تصحيح الخطأ إن وجد و ذلك بتحريك المحرك الخطوي بخطوات دقيقة و الذي يتحكم ببوابة مسيطرة على الوقود الخاص بالمولد، و ذلك بقراءة التردد بفترات زمنية دورية مثل كل 0.3 ثانية و فحص التغيرات، إذا كان التردد أكبر من القيمة المطلوبة. هذا المسيطر و البرنامج المقترح (كود) بلغة (C) سوف يحرك المحرك الخطوي باتجاه عقرب الساعة حتى وصول التردد إلى التردد المطلوب (F0)، أي بكلام آخر إلى 50.00 هيرتز، و إذا القراءة يحصل عليها نقصان من التردد (F0)، فإن المحرك الخطوي سوف يتحرك عكس عقرب للحصول على التردد المطلوب. إن النظام يطبق علمياً بواسطة تنفيذ التصميم المقترح. هذا البحث أنجز سيطرة و تحكم مستقر لغاية 99 % رغم تغير الأحمال و بدقة تردد تصل إلى 0.01 Hz و بمكونات ذات كلفة بسيطة. This study aims at constructing and implementing a new technique for calculating and correcting the frequency deviation in power systems. Several techniques were used to measure frequency deviation. One of them was Arduino Uno card which uses microcontroller ATmega328. This microcontroller board is an easy to use, accurate, economic and flexible solution for measurement problems. The main objective of the work was to measure frequency deviation by microcontroller and displays it on (PC) monitor or small liquid crystal display (LCD) or both. Also, to correct the error if occurred by moving stepper motor with accurate steps which control the fuel gate in the generator, by reading the frequency at periodical time such as per 0.3 second and check the changes, if the frequency is more than required value. The controller and its suggested program (code) in C language will move the stepper motor clockwise (CW) until frequency reaches the required frequency (F0), i.e.50.00 HZ, if the reading gets lower than (F0), and the stepper motor will move counter clockwise (CCW) to get the required frequency. The system is applied practically by implementing the suggested design. This search achieved established control frequency of 99% along any variations in loads with high frequency reaches an accuracy 0.01HZ with low cost components.